Jordan Left Derivation and Centralizer on Skew Matrix Gamma Ring - Shaheen, Rajaa C. (Iraqi Journal of Science, 2021)
We define skew matrix gamma ring and describe the constitution of Jordan left centralizers and derivations on skew matrix gamma ring on a -ring. We also show the properties of these concepts.